Research on Visual Detection Algorithm for Groove Feature Sizes by Means of Structured Light Projection - Zha, Anfei; Lu, Yonghua; Wang, Mingxin; Zhu, Huayu (Transactions of Nanjing University of Aeronautics & Astronautics, 2022)
The visual inspection is an economical and effective method for welding. For measuring the feature sizes of grooves， a method based on line structured light is presented. Firstly， an adaptive algorithm to extract the sub-pixel centerline of structured light stripes is introduced to deal with the uneven width and grayscale distributions of laser stripes， which is based on the quadratic weighted grayscale centroid. By means of region-of-interest （ROI） division and image difference， an image preprocessing algorithm is developed for filtering noise and improving image quality. Furthermore， to acquire geometrical dimensions of various grooves and groove types precisely， the sub-pixel feature point extraction algorithm of grooves is designed. Finally， experimental results of feature size measuring show that the absolute error of measurement is 0.031-0.176 mm， and the relative error of measurement is 0.2%-3.6%.